Bad seeds in the Big Apple: bandits, killers and chaos in New York City, 1920 - 1940 - Downey, Patrick (Cumberland House, 2008)
Gentleman gerald and the dutchman -- Let's misbehave -- Ma Flanagan's boys -- Two worthless diamonds -- Urban cowboys -- Bum, Killer & Ice Wagon LLC -- The Daly show -- The candy kid -- Red scare -- From maiden lane to the tombs -- Don't cry out loud -- Seeing red -- Dishonorable mention 1920-1929 -- New York's most desperate criminal -- Sexy takes a ride -- King of the punks -- College boy -- It came from Massachusetts -- Bride of the mad dog -- The $427,000 payday -- FBI vs. NYPD -- Messing with the mob -- Dishonorable mention 1930-1940